How to evaluate and intervene on stuttering? An analysis of perceptions of specialists in speech therapy - Rehakova Novosadova, Leona; Rama Rodríguez, Alba; Vidal Bouzas, María; Latorre-Cosculluela, Cecilia; Ayllón-Negrillo, Ester; Vieiro Iglesias , Pilar (Revista de Investigación en Logopedia, 2023)
Stuttering is defined as a speech fluency disorder that affects communication. This disorder is complex and can be a major challenge for many speech therapists and other professionals. To date, there is not much research focused on how to assess and intervene in stuttering from the perspective of speech therapy professionals. Precisely for this reason, the objective of this study is to find out what are the main evaluation and intervention methods for stuttering used by speech therapists in the Spanish context and the satisfaction they have with them. For this, a survey was administered in which a total of 123 speech therapists participated and, subsequently, a quantitative analysis of the data obtained was carried out. The results made it possible to discover the different evaluation and intervention methods that are most widely used in the treatment of stuttering, although certain difficulties have been observed in reaching a consensus on their use. In addition, speech therapists claim the need to develop new evaluation instruments and greater collaboration by schools. Therefore, it would be essential to adopt a holistic approach trying to teach subjects with stuttering strategies to deal with fluency and, at the same time, learn to live with and manage the disorder.
Keywords: Assessment; Intervention; Perception; Speech therapist; Stuttering